2020
DOI: 10.1186/s12891-020-03223-3
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term to long-term results of primary arthroscopic Bankart repair for traumatic anterior shoulder instability: a retrospective study

Abstract: Background: The arthroscopic method offers a less invasive technique of Bankart repair for traumatic anterior shoulder instability. The aim of the study is to determine the mid−/long-term functional outcome, failure rates and predictors of failure after primary arthroscopic Bankart repair for traumatic anterior shoulder instability. Methods: A total of 100 patients were primarily operated using arthroscopic Bankart repair after traumatic anterior shoulder instability. Medical records were retrospectively revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
2
31
1
Order By: Relevance
“…This failure rate of 4.17% is comparable with other studies, where the range of failure reported is 2% to 15%. 17,21,24,39 Our hypothesis therefore holds true, as arthroscopic remplissage procedure along with Bankart repair for the treatment of anterior glenohumeral instability with engaging HilleSachs lesion, is associated with good postoperative functional shoulder outcomes, low failure, complication rate, no notable loss of shoulder range of motion.…”
Section: Discussionmentioning
confidence: 81%
“…This failure rate of 4.17% is comparable with other studies, where the range of failure reported is 2% to 15%. 17,21,24,39 Our hypothesis therefore holds true, as arthroscopic remplissage procedure along with Bankart repair for the treatment of anterior glenohumeral instability with engaging HilleSachs lesion, is associated with good postoperative functional shoulder outcomes, low failure, complication rate, no notable loss of shoulder range of motion.…”
Section: Discussionmentioning
confidence: 81%
“…1 . Seven prospective [ 4 , 5 , 10 , 37 , 46 , 48 , 53 ] and 22 retrospective studies [ 1 , 3 , 6 , 7 , 14 17 , 22 25 , 30 , 31 , 33 , 35 , 36 , 43 , 45 , 49 , 57 , 58 ] were included (Table 1 ). The included studies comprised a combined sample size of 4584 shoulders (range 51–670) in 4564 patients (supplementary 2).…”
Section: Resultsmentioning
confidence: 99%
“…38 Hematomas, hardware problems, and nerve damage must all be considered as potential risk factors for missed games and not just recurrence. 38 In addition, this study and others 27,39 have shown that the higher rates of recurrence after Bankart repair may not occur until after 2 years, which may be longer than some AFL careers (career average is 2.9 years). Therefore, some clubs and players may prefer to risk the increased chance of only 1 complication (recurrence) with a Bankart repair over an increased risk profile overall with the Latarjet.…”
Section: Discussionmentioning
confidence: 54%